Pembinaan Guru di Daerah Terpencil - Eddy Subandrijo (Universitas Negeri Malang, 2016)
The role of teachers in isolated remote areas is very important in empowering local human resources. Human character building was partly related to teacher's performance. The teacher's performance in conducting their responsibility depends on the quality of their social-economic conditions. To improve their spirit on daily educational activities, they should be treated by a special management. It means that there must be an equilibrium between career and economic-life and between their right and their responsibility. To implement this concept, all of related institutions should be involved in planning, implementing, and evaluating phases. These institutions are local community, universities, schools, and other institutions belonging to local governments